SOSIAL EKONOMI MASYARAKAT SEKITAR KAMPUS UNIVERSITAS RIAU JL. HR.SOEBRANTAS PEKANBARU - Rika Dayanti; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at around the University of Riau, which includes at Jl. Bangau Sakti, Jl. HR.Soebrantas, Jl. Prof. Mukhtar Lutfi and Jl. Elang Sakti with the title Social Economic Society Around the University of Riau Jl. HR. Soebrantas Pekanbaru. Lately, development of the world education in Indonesia shows a progress positive, including in the city of Pekanbaru, this is marked by the increasing number of educational institution especially at the level collage, one of which is the University of Riau which has been established since 1962, in its development the existence of campuses located on the outskirts of the city has led to emergence of various forms of economic activity and has an impact on the condition of the surrounding society, especially in social economic conditions.This study aims to find out what forms of economic aktivity are that same time how social economic confessions of the society around University of Riau. The theory used in this research are the core area theory of John Friedman, while the method usedis quantitative descriptive by using observation techniques and questionnaires. The results showed that from 82 respondents, 51 of them opened businesses in the trade sector and the remaining 31 respondents opened businesses in the service sector, beside that there is a dependency between the society around the campus and campus ativities, where if the campus activities off they also take a holiday. As for the socio economic conditions of the society around University of Riau in the middle level, becausebased on the datait can be seen that themajority of respondents income is Rp.2.500.000- Rp.5.000.000/month that is much as 41 respondents with education graduating from high school which is 40 respondents. While the ownership status of the residence is rented much as 60 respondents and ownership of private vehicles is a motorcycle as much 64 respondents.Keywords: Social Economic, Society, University of Riau